The Development of a Community of Inquiry Over Time in an Online Course: Understanding the Progression and Integration of Social, Cognitive and Teaching Presence - Akyol, Zehra; Garrison, Randy (Online Learning, 2008)
The purpose of this study was to explore the dynamics of an online educational experience through the lens of the Community of Inquiry framework. Transcript analysis of online discussion postings and the Community of Inquiry survey were applied to understand the progression and integration of each of the Community of Inquiry presences. The results indicated a significant change in teaching and social presence categories over time. Moreover, survey results yielded significant relationships among teaching presence, cognitive presence and social presence, and students’ perceived learning and satisfaction in the course. The findings have important implications theoretically in terms of confirming the framework and practically by identifying the dynamics of each of the presences and their association with perceived learning and satisfaction.